Pathways into and out of homelessness among people with severe mental illness in rural Ethiopia: a qualitative study - Smartt, Caroline (BMC Public Health, 2021)
BACKGROUND: Little is known about the pathways followed into and out of homelessness among people with experience of severe mental illness (SMI) living in rural, low-income country settings. Understanding these pathways is essential for the development of effective interventions to address homelessness and promote recovery. The aim of this study was to explore pathways into and out of homelessness in people with SMI in rural Ethiopia. METHODS: In-depth interviews were conducted with 15 people with SMI who had experienced homelessness and 11 caregivers. Study participants were identified through their participation in the PRIME project, which implemented a multi-component district level plan to improve access to mental health care in primary care in Sodo district, Ethiopia. People enrolled in PRIME who were diagnosed with SMI (schizophrenia, schizoaffective disorder or bipolar disorder) and who had reported experiencing homelessness at recruitment formed the sampling frame for this qualitative study. We used OpenCode 4.0 and Microsoft Excel for data management. Thematic analysis was conducted using an inductive approach. RESULTS: Study participants reported different patterns of homelessness, with some having experienced chronic and others an intermittent course. Periods of homelessness occurred when family resources were overwhelmed or not meeting the needs of the person with SMI. The most important pathways into homelessness were reported to result from family conflict and the worsening of mental ill health, interplaying with substance use in many cases. Participants also mentioned escape and/or wanting a change in environment, financial problems, and discrimination from the community as contributing to them leaving the home. Pathways out of homelessness included contact with (mental and physical) health care as a catalyst to the mobilization of other supports, family and community intervention, and self-initiated return. CONCLUSIONS: Homelessness in people with SMI in this rural setting reflected complex health and social needs that were not matched by adequate care and support. Our study findings indicate that interventions to prevent and tackle homelessness in this and similar settings ought to focus on increasing family support, and ensuring access to acceptable and suitable housing, mental health care and social support. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10629-8.